The Utilization of the Cultural Heritage in Mamdouh Adwan's Poetry - Hasan, Muhammad; Ali, Muhammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The cultural heritage image, which is one of the modern figurative images, has been increasingly used in modern Arabic literature which finds in traditions a rich source for figurative image. This research deals with one of the mechanisms to employ this image in Mamdouh Adwan's poetry, which is the cumulative employment. The research has chosen one example highlighting the significance of this partial image in constructing integrated scenery which, in turn, produces a full image. Moreover, this research confirms the importance of cultural heritage in providing the poetic image with components and elements that have specific semantic nature. Consequently, the interaction between the author and the cultural heritage becomes effective, at the level of the image, in order to produce poetic vision of a traditional reference. However, it does not eliminate the originality of the poet; rather it deepens the content and gives the form new artistic devices.